VIRTUAL MEETINGS UNLEASHED: A JOURNEY TOWARDS LECTURERS' SATISFACTION IN ONLINE ASYNCHRONOUS BASED LEARNING - Sari, Novi Yulinda; Gani, Sofyan A; Samad, Iskandar Abdul (Language Circle: Journal of Language and Literature, 2023)
While online learning has advantages, it also poses challenges, notably the lack of personal connection between educators and students, impacting the psychological aspect of learning. The pandemic period further highlighted issues like technological disparities and limited lecturers' competence in using learning applications, affecting the effectiveness of online education. Ensuring a quality educational experience is crucial. This study examines lecturers' satisfaction with videoconference-based virtual meeting applications in teaching-learning activities at a private college. Using a qualitative approach with semi-structured interviews and thematic analysis, the study explored lecturers' satisfaction. The findings indicate that while virtual meetings might not guarantee improvements in students' English skills, the lecturers were satisfied with the system's implementation. Collaborative teaching through virtual meetings balanced asynchronous learning with direct feedback, fostering class interaction and satisfying the urge for distance learning. The study sheds light on lecturers' satisfaction with virtual meeting applications, underscoring the need to address challenges to enhance online education's effectiveness and quality.